Analysis of the Influence of Changes in the Profession of the Bungus Fishing Community on the Quality of Human Resources in the Coastal Area of Padang City - Marta Widian Sari; Andry Novrianto (Enrichment : Journal of Management, 2020)
The purpose of this study was to see the effect of income and technology use on the quality of human resources in the coastal area of ​​Padang city through the professional changes of the Bungus fishermen community to become marine tourism guides as an intervening variable. The population in this study is the Bungus fishermen community who become marine tour guides. The sampling method used was proportional random sampling of 100 people. Data processing with SmartPLS 3.0.The results of this study are stating that 'income is not mediated by the professional change of the Bungus fishermen community to become marine tourism guides on the quality of human resources in the coastal area of ​​Padang city. And furthermore the relationship between the use of technology on the quality of human resources in the coastal area of ​​the city of Padang and the professional change of the Bungus fishing community to become marine tourism guides as a variable that intervenes in the statement that the use of technology is mediated by the professional change of the Bungus fishing community to become marine tourism guides on the quality of regional human resources. Padang City Coastal.